Removal of Bumiputera Shareholding Restriction: Does it affect the stock market performance? - Leow, Shoun Shin (2011)
The Malaysian Government has recently announced the removal of 30% Bumiputera equity restriction which was enforced under NEP policy and monitor under FIC, a special department monitoring the Bumiputera shareholding in public listed companies. This paper intends to study the effects of loosening policy on the Stock Market performances prior to policy change. We shall look into the history of such formulation of the policy. Then, the paper will discuss on literature review on other relevant research findings, which could help this study to formulate the testing models. An empirical research will be conducted using Event Study Analysis to support the theoretical findings. Data will be collected from the Malaysian Stock Market. Finally, the paper shall sums up with the theoretical and empirical findings, and some suggestion of further studies on this topic.